Experimental Study of Impregnated Diamond Bit Wear - Huang, Rui (Curtin University, 2025)
This research addresses the challenge of assessing bit wear state during drilling by developing a novel experimental methodology and performing extensive lab-scale drilling experiments. A conceptual wear model with three regimes—polishing dominant, fracturing dominant, and pull-out dominant—relates depth of cut, rock hardness, and fluid viscosity to wear mechanisms and rates. This framework optimizes drilling performance by predicting wear behavior and selecting the optimal depth of cut under various conditions, distinguishing effects of bit wear from rock properties.